Genetic Relatedness Of Local Varieties Of Rice South Sumatra Based On Polymerase Chain Reaction – Random Amplified Polymorphic DNA (PCR-RAPD) - Laila Hanum; Yuanita Windusari; Muharni Muharni; Fikri Adriansyah (Sriwijaya Journal of Environment, 2017)
Diversity 22 local varieties of rice South Sumatra has the potential to be developed into rice varieties. The similarity (similarity) among 22 local varieties of rice South Sumatra became one of the obstacles for scientists to develop rice varieties. One solution to this problem is to determine the genetic relatedness between 22 rice local vaietas South Sumatra. Identification of genetic relatedness among 22 local varieties of rice South Sumatra can be carried out using PCR-RAPD. This study aims to determine the phylogenetic relationship among 22 local varieties of rice South Sumatra. This research about DNA isolation and visualitation has been carried out in August 2015 until December 2015 in Microbiology Laboratory and Laboratory of Genetics and Biotechnology, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Sriwijaya and research about DNA quality and quantity test and PCR-RAPD has been done in Biotechnology Labotory Faculty of Mathematics and Natural Sciences, Sriwijaya University. Obtained 22 local varieties of rice accessions South Sumatra. Genetic relatedness identified using PCR-RAPD technique. 7 primer (OPA, OPA-9, OPA-10, OPA-13, OPA-16, OPA-19, OPB-8) was used for amplification. Local varieties of rice South Sumatra is divided into two major groups in association coefficient of 0.76, namely groups A and B. Group A consists of groups A1 and A2 in association coefficient of 0.78. In the large group B also consists of two groups: the B1 and B2 in association coefficient of 0.84. Local varieties of rice genetic relatedness South Sumatra are not influenced by geographical location.Keywords: Local Varieties Of Rice South Sumatra, Genetic Relatedness,  PCR-RAPD